2007
DOI: 10.2307/25549738
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Risk to HIV Infection among Adolescents in Uganda: Are They Related to Sexual Behaviour?

Abstract: Uganda has been hailed as a success story in the fight against HIV that has seen a reversal in prevalence from a peak of 15% in 1991 to about 6.5% currently Since 1992, the largest and most consistent declines in HIV have occurred among the 15-19-year-olds. While many studies have examined how key behavior changes (Abstinence, Be faithful and Condom use) have contributed to the decline in HIV prevalence, few have studied the relationship between sexual behaviors and risk perception. Using data from the 2004 Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 15 publications
8
33
5
Order By: Relevance
“…In this study we found that almost half of the students interviewed perceived themselves to be at risk of contracting HIV. Our findings are slightly lower than earlier findings from Kibombo and colleagues who report that among adolescents aged 15-19 years, 72% of the females compared to 55% perceived themselves as being at risk of contracting HIV [6]. The discrepancy between our findings and those reported by Kibombo and colleagues may be explained in several ways.…”
Section: Sexual Behaviors Of Secondary School Studentscontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study we found that almost half of the students interviewed perceived themselves to be at risk of contracting HIV. Our findings are slightly lower than earlier findings from Kibombo and colleagues who report that among adolescents aged 15-19 years, 72% of the females compared to 55% perceived themselves as being at risk of contracting HIV [6]. The discrepancy between our findings and those reported by Kibombo and colleagues may be explained in several ways.…”
Section: Sexual Behaviors Of Secondary School Studentscontrasting
confidence: 99%
“…This behavior raises a suspicion within the individual of a possibility of having been exposed to HIV. Kibombo and colleagues found a highly significant association between perceived risk of contracting HIV and sexual behaviors of male adolescents lending support to the above assertion [6]. In regard to the finding that those who had ever taken an HIV test were more likely to perceive themselves to be at risk of contracting HIV, this should not be surprising because the fear of having been exposed might have been the motive behind seeking testing services.…”
Section: Factors Associated With Perceived Risk Of Contracting Hivmentioning
confidence: 85%
See 2 more Smart Citations
“…(Mair, 1934) Although not entirely powerless within relationships, most authors agree that once the brideprice or monies and gifts are exchanged in adult relationships, women lose much of their power to control their sexual and reproductive life to their husbands, and in relationships with men more generally (Blanc, 2001;Blanc & Wolff, 2001;Mantell et al, 2006;Miles, 1993;Nyanzi, Nyanzi, Wolff, & Whitworth, 2005;Rao Gupta, 2000;Wolff, Blanc, & Gage, 2000;Wolff, Blanc, & SsekamatteSsebuliba, 2000). This power differential between men and women is cited as the fundamental cause of women's disproportional burden of sexually transmitted infections (STIs) relative to men in this region (Kibombo, Neema, & Ahmed, 2007;Rao Gupta, 2002).…”
mentioning
confidence: 99%